Neoadjuvant Strategies: Locally Advanced Rectal Cancer - Ahmed, Shahab; Eng, Cathy (Clinics in Colon and Rectal Surgery, 2017)
Colorectal cancer is one of the major leading causes of death in both men and women. The successful management of colon or rectal cancer demands a multidisciplinary approach. In the last few years, significant improvement has been noticed in the management of localized rectal cancer to reduce local recurrence and obtain complete pathological response following appropriate surgical steps, if necessary. Implementation of neoadjuvant therapy not only enhances disease control, it may also ensure sphincter preserving procedures or organ-preserving options. This article principally concentrates on the current neoadjuvant treatment for locally advanced rectal cancer and the prognostic outcomes of such therapy, including a discussion on the historical perspective.
Keywords: colorectal cancer; rectal cancer; neoadjuvant chemoradiation; adjuvant chemotherapy; survival